Negative Pressure Wound Therapy in the Management of Combat Wounds: A Critical Review - Maurya, Sanjay (Adv Wound Care (New Rochelle), 2016)
Significance: Wounds sustained in a combat trauma often result in a composite tissue loss. Combat injuries, due to high energy transfer to tissues, lead to trauma at multiple anatomical sites. An early wound cover is associated with lower rate of infections and a faster wound healing. The concept of negative pressure wound therapy (NPWT) in the management of combat-related wounds has evolved from the civilian trauma and the wounds from nontraumatic etiologies. Recent Advances: Encouraged by the results of NPWT in noncombat-related wounds, the military surgeons during Operation Iraqi Freedom and Operation Enduring Freedom used this novel method in a large percentage of combat wounds, with gratifying results. The mechanism of NPWT in wound healing is multifactorial and often complex reconstructive procedure can be avoided in a combat trauma setting. Critical Issues: Wounds sustained in military trauma are heavily contaminated with dirt, patient clothing, and frequently associated with extensive soft tissue loss and osseous destruction. Delay in evacuation during an ongoing conflict carries the risk of systemic infection. Early debridement is indicated followed by delayed closure of wounds. NPWT helps to provide temporary wound cover during the interim period of debridement and wound closure. Future Directions: Future area of research in combat wounds is related to abdominal trauma with loss of abdominal wall. The concept of negative pressure incisional management system in patients with a high risk of wound breakdown following surgery is under review, and may be of relevance in combat wounds.